2015
DOI: 10.2214/ajr.14.14166
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Follow-Up FDG PET or PET/CT in Patients With Head and Neck Cancer After Definitive Treatment: A Systematic Review and Meta-Analysis

Abstract: The high diagnostic performance of FDG PET/CT in detecting recurrence in curatively treated patients with head and neck cancer supports its use in clinical practice for patient follow-up. Further studies are needed to evaluate the prognostic utility of PET/CT in the follow-up of head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 41 publications
5
55
1
1
Order By: Relevance
“…7,9 Postoperative followup with PET/CT enables early detection of tumor recurrence, guides endoscopic biopsies, and allows selection of treatment for better survival and lower morbidity of those patients. 7,9 Postoperative followup with PET/CT enables early detection of tumor recurrence, guides endoscopic biopsies, and allows selection of treatment for better survival and lower morbidity of those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 Postoperative followup with PET/CT enables early detection of tumor recurrence, guides endoscopic biopsies, and allows selection of treatment for better survival and lower morbidity of those patients. 7,9 Postoperative followup with PET/CT enables early detection of tumor recurrence, guides endoscopic biopsies, and allows selection of treatment for better survival and lower morbidity of those patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] An important advantage of PET/CT is that a whole-body scan allows for the detection of distant metastases and unexpected secondary cancers. Positron emission tomography (PET) and, in particular, combined PET-computed tomography (PET/CT) have become popular as useful diagnostic and prognostic tools for pretreatment staging, radiotherapy planning, measuring treatment response for residual or recurrent disease, and monitoring posttreatment follow-up results in various head and neck malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…To support this hypothesis, our team has already shown in several series the high performance of FDG‐PET/CT to diagnose subclinical relapse with an overall accuracy varying from 89% to 97% . Furthermore, a recent meta‐analysis of seven studies comprising 920 patients without clinical symptoms also revealed respective pooled sensitivity and specificity of 89% and 90%, respectively, of FDG‐PET/CT in detecting asymptomatic recurrence after treatment . However, we admit that comparing TNR PET and contrast enhancement is not completely relevant, but we did not find any other quantitative value to compare.…”
Section: Discussionmentioning
confidence: 74%
“…FDG-PET is frequently used for treatment response assessment with high sensitivity but lower specificity [45]. Compared to FDG-PET, ADC can be performed earlier to assess treatment response.…”
Section: Discussionmentioning
confidence: 99%